2014
DOI: 10.1038/nn.3697
|View full text |Cite
|
Sign up to set email alerts
|

Single App knock-in mouse models of Alzheimer's disease

Abstract: Experimental studies of Alzheimer's disease have largely depended on transgenic mice overexpressing amyloid precursor protein (APP). These mice, however, suffer from artificial phenotypes because, in addition to amyloid β peptide (Aβ), they overproduce other APP fragments. We generated knock-in mice that harbor Swedish and Beyreuther/Iberian mutations with and without the Arctic mutation in the APP gene. The mice showed typical Aβ pathology, neuroinflammation and memory impairment in an age-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

103
1,516
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 1,012 publications
(1,629 citation statements)
references
References 25 publications
103
1,516
8
2
Order By: Relevance
“…Due to the increase in CTF‐β and concomitant decrease of CTF‐α in the App knock‐in mice, the total amount of CTF in App knock‐in mice remains the same as in wild‐type mice. To examine the effect of increased CTF‐β and s APP β in this case, App NL mice were generated that carried only the Swedish mutation and we confirmed that this amount of CTF‐β and s APP β exert no effects on the pathology or cognitive function of the mice (Saito et al , 2014; Masuda et al , 2016). The high levels of Aβ 42 in App NL‐F mice led to pathological Aβ deposition in the cerebral cortex and hippocampus, which was accompanied by enhanced neuroinflammation, that is, infiltration of astrocytes and microglia that surround plaques from 6 months of age.…”
Section: Second‐generation Mouse Modelsmentioning
confidence: 66%
See 4 more Smart Citations
“…Due to the increase in CTF‐β and concomitant decrease of CTF‐α in the App knock‐in mice, the total amount of CTF in App knock‐in mice remains the same as in wild‐type mice. To examine the effect of increased CTF‐β and s APP β in this case, App NL mice were generated that carried only the Swedish mutation and we confirmed that this amount of CTF‐β and s APP β exert no effects on the pathology or cognitive function of the mice (Saito et al , 2014; Masuda et al , 2016). The high levels of Aβ 42 in App NL‐F mice led to pathological Aβ deposition in the cerebral cortex and hippocampus, which was accompanied by enhanced neuroinflammation, that is, infiltration of astrocytes and microglia that surround plaques from 6 months of age.…”
Section: Second‐generation Mouse Modelsmentioning
confidence: 66%
“…Crossbreeding with other mutant mice can generate additional artificial phenotype(s) (Higuchi et al , 2012; Saito et al , 2014). Refer to section “Limitations of first‐generation mouse models” for details.…”
Section: Limitations Of First‐generation Mouse Modelsmentioning
confidence: 99%
See 3 more Smart Citations